2020
DOI: 10.1038/s41598-020-63087-4
|View full text |Cite
|
Sign up to set email alerts
|

De novo sensitization during subcutaneous allergen specific immunotherapy - an analysis of 51 cases of SCIT and 33 symptomatically treated controls

Abstract: Since the beneficial implementation of allergen specific subcutaneous immunotherapy (SCIT), there are only a few studies on the risk of SCIT-induced neosensitizations. In 51 patients, we retrospectively analyzed sige and sigG patterns by a multiplex eLiSA as well as demographic and clinical features before and after SCIT. 33 allergic patients, who only received symptomatic treatment, served as controls. In 12 of 51 SCIT-treated patients (24%), we found new sIgE against allergen components of the allergen sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
2
3
0
1
Order By: Relevance
“…No major change was observed in prevalence of IgE reactivity after 1 year treatment. In agreement with previous studies reporting limited neosensitizations in patients undergoing AIT, 33,34,46,47 we observed in the present study, a few patients with IgE levels rising above the 0.3 ISU positivity threshold. In most cases, the induction of IgE was counterbalanced by an increase of IgG/IgG 4 .…”
Section: Discussionsupporting
confidence: 94%
“…No major change was observed in prevalence of IgE reactivity after 1 year treatment. In agreement with previous studies reporting limited neosensitizations in patients undergoing AIT, 33,34,46,47 we observed in the present study, a few patients with IgE levels rising above the 0.3 ISU positivity threshold. In most cases, the induction of IgE was counterbalanced by an increase of IgG/IgG 4 .…”
Section: Discussionsupporting
confidence: 94%
“… 15 , 22 However, the thesis is challenged by Potapova et al, who reported a significant rise in IgG and IgG4 against Der p 1, 2, 23 as well as Der p 4, 15, 18 and 37 during HDM SLIT. 14 Finally, it might be possible that neosensitizations in the course of AIT develop over a period of time longer than 12 months, which was raised by Gellich et al 19 This possibility was considered, and the authors of the present study continued observation of the study group. However, this investigation was conducted with unmatched stored sera in which the controls were not necessarily selected by the same criteria.…”
Section: Discussionmentioning
confidence: 59%
“…Running counter to both the abovementioned and our own observations is the paper of Gellrich et al, regarding the development of neosensitizations in the cohort of 51 patients subject to SCIT with different groups of allergens for over 12 months (Fagales (N = 18), Poaceae (N = 19) and HDM (N = 14)), which suggests that such occurrences may take place. 19 …”
Section: Discussionmentioning
confidence: 99%
“…A categorical variable was generated from duration of mopane worm harvesting whereby a period of 2 years was considered a reasonable period in which a neo-sensitisation can occur. This was derived from studies reporting sensitisation to neo-allergens following immunotherapy [ 47 , 48 ]. Participants reporting a harvesting duration of less than 2 years, including no harvesting at all, were included in the comparison group for this variable.…”
Section: Methodsmentioning
confidence: 99%